Antiplatelet therapy in Coronary Artery Disease - Bakhromkhon Aniskhonovich Alyavi, Kamilovich Uzokov; OminaYusupqizi Mukhitdinova (Institute of Medico-legal Publications Pvt Ltd, 2021)
Coronary artery disease (CAD) is the leading cause of morbidity and mortality worldwide. Platelets play crucial role for the development of thrombus in the atherosclerotic narrowed arteries. This review article summarizes modern antiplatelet therapies particularly, aspirin and clopidogrel in coronary artery disease, platelet aggregation, possible risk factors, their mechanism of action and pharmacological properties. In addition, it provides up to date information regarding acetyl salicylic acid - aspirin and representative of the thienopyridine – clopidogrel and their role in patients with CAD.